Displaced Patella Fractures - Della Rocca, Gregory J. (The Journal of Knee Surgery, 2013)
Displaced patella fractures often result in disruption of the extensor mechanism of the knee. An intact extensor mechanism is a requirement for unassisted gait. Therefore, operative treatment of the displaced patella fracture is generally recommended. The evaluation of the patella fracture patient includes examination of extensor mechanism integrity. Operative management of patella fractures normally includes open reduction with internal fixation, although partial patellectomy is occasionally performed, with advancement of quadriceps tendon or patellar ligament to the fracture bed. Open reduction with internal fixation has historically been performed utilizing anterior tension band wiring, although comminution of the fracture occasionally makes this fixation construct inadequate. Supplementation or replacement of the tension band wire construct with interfragmentary screws, cerclage wire or suture, and/or plate-and-screw constructs may add to the stability of the fixation construct. Arthrosis of the patellofemoral joint is very common after healing of patella fractures, and substantial functional deficits may persist long after fracture healing has occurred.
Keywords: patella fracture; patellectomy; fracture fixation